2020
DOI: 10.1093/gbe/evaa101
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal-Level Genome Assembly of the Sea Urchin Lytechinus variegatus Substantially Improves Functional Genomic Analyses

Abstract: Lytechinus variegatus is a camarodont sea urchin found widely throughout the western Atlantic Ocean in a variety of shallow-water marine habitats. Its distribution, abundance, and amenability to developmental perturbation make it a popular model for ecologists and developmental biologists. Here, we present a chromosomal-level genome assembly of L. variegatus generated from a combination of PacBio long reads, 10X Genomics sequencing, and HiC chromatin interaction sequencing. We show L. variegatus has 19 chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 33 publications
3
60
1
Order By: Relevance
“…In this study, a large number of genome fragments were obtained for M. nudus by using GBS. By analyzing the DNA base composition, the percentage of GC content was up to 41%, which was higher than that of the reported sea urchin, including Strongylocentrotus purpuratus (36.9%) ( Sodergren et al, 2006 ), and Lytechinus variegatus (36.1%) ( Davidson et al, 2020 ). Considering that genomic GC content is closely associated with genome size and significantly affects the genome functioning and species ecology ( Šmarda et al, 2014 ), this result suggested that M. nudus may have a more complex genome than S. purpuratus and L. variegatus .…”
Section: Discussioncontrasting
confidence: 57%
“…In this study, a large number of genome fragments were obtained for M. nudus by using GBS. By analyzing the DNA base composition, the percentage of GC content was up to 41%, which was higher than that of the reported sea urchin, including Strongylocentrotus purpuratus (36.9%) ( Sodergren et al, 2006 ), and Lytechinus variegatus (36.1%) ( Davidson et al, 2020 ). Considering that genomic GC content is closely associated with genome size and significantly affects the genome functioning and species ecology ( Šmarda et al, 2014 ), this result suggested that M. nudus may have a more complex genome than S. purpuratus and L. variegatus .…”
Section: Discussioncontrasting
confidence: 57%
“…According to a standard analysis pipeline (Massri et al, 2021), we mapped reads to the Lv3.0 genome (Davidson et al, 2020), with the 10x Cellranger pipeline and filtered out low quality cells using Seurat (Butler et al, 2018; Stuart et al, 2019). In total 50,935 cells remained and were used for the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal transport method was then used to follow temporal profiles of cell fate specification, and to address several unanswered questions related to gene regulation in development. It was of great value to have a well annotated, high quality genome in order to produce gene calls with high fidelity (Davidson et al, 2020). With these quality checks complete, we built on Waddington-OT (Schiebinger et al, 2019) to devise a number of novel computational analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences for insulin related peptides and their likely receptors were identified from a number of Ambulacraria species. This was done using the Artemis program ( Rutherford et al, 2000 ) and the BLAST+ program ( https://blast.ncbi.nlm.nih.gov/Blast.cgi ) on publicly available genome sequences from the feather star Anneissia japonica , the sea urchins Lytechinus variegatus ( Davidson et al, 2020 ) and Strongylocentrus purpuratus ( Sea Urchin Genome Sequencing Consortium, 2006 ), the sea cucumbers Apostichopus japonicus ( Jo et al, 2017 ; Zhang et al, 2017 ) and Holothuria glaberrima , the sea stars Acanthaster planci ( Hall et al, 2017 ) , Pisaster ochraceus ( Ruiz-Ramos et al, 2020 ) and Patiria miniata , the brittle star Ophiothrix spiculata and the hemichordates Saccoglossus kowalevskii and Ptychodera flava ( Simakov et al, 2015 ). The genomes were downloaded from https://www.ncbi.nlm.nih.gov/genome .…”
Section: Methodsmentioning
confidence: 99%